farid wajdi Dengan hormat, kami mengajukan naskah artikel ilmiah berjudul “Ketika Kata Menjadi Mukjizat: Menjelajahi Keunikan Al-Qur’an” untuk dipertimbangkan dalam publikasi Jurnal QOF. Artikel ini membahas aspek i'jaz Al-Qur’an dari pendekatan linguistik klasik dan: Menjelajahi Keunikan Al-Qur’an dari Perspektif Linguistik Klasik dan Modern - Ravi, Muhammadfaridwajdi Sabil (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The Qur'an as the holy book of Muslims has a uniqueness that distinguishes it from other books, both in terms of language, structure, and content of meaning. This study aims to explore the miraculous aspects of the Qur'an through a linguistic approach and classical Arabic literature. The method used is descriptive-qualitative analysis with a hermeneutic approach to the texts of the Qur'an and classical literature on the i'jaz of the Qur'an. The results of the study indicate that the miracle of the Qur'an lies in the uniqueness of its language structure that cannot be imitated, the harmony between sound and meaning, and the consistency of the narrative that is maintained throughout the 23 years of revelation. The conclusion of this study confirms that the Qur'an has unique linguistic characteristics that prove its authenticity and miracle as divine revelation.